2023
DOI: 10.1111/cup.14439
|View full text |Cite|
|
Sign up to set email alerts
|

IRF8 may be a useful marker for blastic plasmacytoid dendritic cell neoplasm, especially with weak CD123 expression

Abstract: We highlight the utility of interferon regulatory factor 8 (IRF8), a novel marker of monocytic and dendritic cell lineages, in the diagnosis of a case of blastic plasmacytoid dendritic cell neoplasm (BPDCN) presenting initially in the skin. A 60-year-old male with a previous history of myelodysplastic syndrome presented with cutaneous nodules on chest and scalp. A punch biopsy specimen of a skin nodule showed a diffuse dermal infiltrate of atypical mononuclear cells. The neoplastic cells expressed CD4, CD56, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The cell nuclei are round or irregular, the chromatin is finely detailed, the cytoplasm is basophilic, devoid of granules, and can have characteristic pseudopodia and mirror-image morphology, or can present a lymphoma-like or primitive monocyte-like morphological type. 19,20 However, a study found that only 44.4% of patients had typical BPDCN pathological morphology, with the remainder exhibiting morphological diversity. 21 This case showed primitive cell morphology, the nuclei were quasi-circular, the nucleoli were prominent, partially distributed in clusters, some cells had pseudopodial-like protrusions in the cytoplasm, were stained bluer, and the morphology leaned towards lymphoma-like, which is not typical, necessitating differentiation with immunophenotypic features.…”
Section: Discussionmentioning
confidence: 99%
“…The cell nuclei are round or irregular, the chromatin is finely detailed, the cytoplasm is basophilic, devoid of granules, and can have characteristic pseudopodia and mirror-image morphology, or can present a lymphoma-like or primitive monocyte-like morphological type. 19,20 However, a study found that only 44.4% of patients had typical BPDCN pathological morphology, with the remainder exhibiting morphological diversity. 21 This case showed primitive cell morphology, the nuclei were quasi-circular, the nucleoli were prominent, partially distributed in clusters, some cells had pseudopodial-like protrusions in the cytoplasm, were stained bluer, and the morphology leaned towards lymphoma-like, which is not typical, necessitating differentiation with immunophenotypic features.…”
Section: Discussionmentioning
confidence: 99%